THE DEVELOPMENTAL STATE IN NIGERIA - Eyikeshi Damue Wavie (Graduate School of International Studies Ajou University, 2014)
ABSTRACT The petroleum sector in Nigeria for long has been the mainstay of the economy and the mean generator of foreign exchange revenues. For several decades, various policies have been put in place to empower this sector as the engine of growth of the Nigerian economy. This policies range from the petroleum indigenization policy of 1969 to the petroleum domiciliation policy of the early 90’s and most recently the 2010 local content policy in the oil and gas sector. The petroleum sector most often has been criticized for not contributing substantially in reducing poverty, economic inequality and unemployment as the life wire of the economy. In fact, in the last two decade, the petroleum sector in Nigeria has enjoyed windfalls in crude oil export revenues as a result of trade boom in mineral resources (Petroleum) in the World market. This increment in crude oil export revenues have been criticized for not being proportionate to poverty reduction, economic inequality and unemployment. In an effort to foster the petroleum sector as the engine of growth of the Nigerian economy, a local content policy was instituted at the dawn of the last decade to serve as the new economic growth order in the petroleum sector. The Nigerian local content policy in the oil and gas sector is just four years old and making forgone conclusions on its influence in addressing poverty, unemployment and economic inequality is unfair but there are however some gaps in the new policy that need to be addressed. This study will explain why despite improvements in petroleum revenues and the enactment of a local content policy in the petroleum sector, this has not translated into substantial reduction in poverty and subsequently low level of local content Key words: Developmental states; Local content policy; petroleum industry
학위논문(석사)--아주대학교 국제대학원 :국제개발협력과,2014. 8
Keywords: IDC